Evaluasi Terhadap Buku Ajar Bahasa Arab Madrasah di Indonesia Berbasis Kurikulum 2013 - Nana Jumhana (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Textbooks are an essential element in the learning process. Good or low quality will affect the quality of education. Therefore this research is considered necessary, namely evaluating textbooks published by the Ministry of Religion in 2014. The problem in this study is the extent to which Arabic textbooks published by the Ministry of Religion implement 2013 in all madrasas in Indonesia. The conclusion of this study about the three Arabic textbooks is that there is no relation between the three textbooks' approaches with the Regulation of the Minister of Religion. No. 165 approaches, the three textbooks have the feasibility of the content of the material substance and have included the characteristics of the 2013 curriculum implementation. This research is a descriptive study, where the primary data source is Arabic textbooks—included in the category of non-interactive research or analytical research, using the Content Analysis method.